The Role of Administration in Managing School Archieves at SMK Veteran - Nurzannah, Ikke (JIEM (Journal of Islamic Education Management), 2021)
THE ROLE OF ADMINISTRATION IN MANAGING SCHOOL ARCHIVES AT SMK VETERAN CIREBON CITYABSTRACTEvery school certainly has an administration in it which is tasked with carrying out school administrative activities, including archiving activities.  However, in this case, there are many institutions that pay less attention to archives, including schools.  In this case, the administration really needs to hold archives at school.  Archives as a source of written information that can help remind us of previous information.  The purpose of this study is to find out how the administration in carrying out its role in managing school archives and find out what are the obstacles experienced by the administration in managing archives.  This research is a descriptive qualitative research with 2 informants, namely the head of administration, Mr. Ranita Ruswanda (Pak Dede) and the administrative staff of Mr. Darga. The data collection techniques in this study were using interviews, observations, and documentation.  The results of this study are the administration has done well in managing school archives although there are still some shortcomings in it.  Based on the results of the study, it can be concluded that the administration of Veterans Vocational School has carried out its role well in terms of managing school archives, but it needs to be improved again because in order to optimize school administrative activities.  Keywords: Administration, Management, Archives  PERAN TATA USAHA DALAM MENGELOLA ARSIP SEKOLAH DI SMK VETERAN KOTA CIREBON  ABSTRAKSetiap sekolah tentunya memiliki tata usaha di dalamnya yang bertugas untuk melakukan kegiatan administrasi sekolah termaksud dalam kegiatan kearsipan. Namun dalam hal ini banyak sekali lembaga yang kurang memperhatikan kearsipan tidak terkecuali sekolah. Dalam hal ini tata usaha sangatlah perlu mengadakan kearsipan disekolah. Arsip sebagai sumber informasi tertulis yang dapat membantu mengingatkan kita kepada informasi-informasi terdahulu. Tujuan dari penelitian ini yaitu untuk mengetahui bagaimana tata usaha dalam menjalankan perannya dalam mengelola arsip sekolah dan mengetahui apa saja kendala-kendala yang dialami tata usaha dalam mengelola arsip. Penelitian ini merupakan penelitian kualitatif deskriptif. Teknik pengumpulan data dalam penelitian ini yaitu dengan menggunakan wawancara, observasi, dan dokumentasi. Hasil penelitian ini tata usaha sudah melakukan dengan baik pengelolaan arsip sekolah walau masih terdapat beberapa kekurangan di dalamnya. Berdasarkan hasil penelitian dapat disimpulkan bahwa tata usaha SMK Veteran sudah melaksanakan perannya dengan baik dalam hal mengelola arsip sekolah hanya saja perlu ditingkatkan lagi karena agar dapat lebih mengoptimalkan kegiatan administrasi sekolah. Kata Kunci : Tata Usaha, Pengelolaan, Arsip